Large branchiopod (Crustacea: Branchiopoda) egg morphology of Western Ghats, Maharashtra, India - Padhye, Sameer; Timms, Brian; Ghate, Hemant V. (Zootaxa, 2016)
The eggs of many large branchiopods have taxonomic value and are commonly used as traits in species and/or generic descriptions. In this paper we present detailed descriptions and SEMs of resting eggs of seven of the eight species of large branchiopods found in the Western Ghats of Maharashtra, India. We highlight the inter- and intrapopulation egg morphological variation in Streptocephalus.